2020
DOI: 10.1002/tox.23020
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin induces autophagy in myelodysplastic bone marrow including hematopoietic stem/progenitor compartment

Abstract: Myelodysplastic syndrome (MDS) is regarded as a spectrum of bone marrow failure disorders that share hemato‐pathological state of cellular dysplasia and cytopenia. The modern treatment of cancers like chemotherapy and radiation therapy sometimes severely pounce on the basic hematopoietic stem/progenitor cellular (HSPC) compartment which gradually disclose the clinical symptoms of MDS. The present study involves flowcytometric protein expression analysis of insulin growth factor receptor (IGFR), PI3K‐Akt‐mTOR p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…However, in contrast with our findings, their study reported that quercetin treatment induced protein aggregation, mostly inside the nucleus [ 29 ]. Induction of autophagy by quercetin has been observed in several tissues and diseases, including diabetic nephropathy [ 30 ], oocytes from aged mice [ 31 ], intervertebral disc degeneration [ 32 ], myelodysplastic bone marrow [ 33 ], and human retinal pigment epithelial cells [ 34 ], while one study reported that quercetin attenuated autophagy in a rat model of traumatic brain injury [ 35 ]. Regardless of these previous studies, here we performed a comprehensive set of autophagy assays that unquestionably proved the effect of quercetin on autophagy for the first time [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast with our findings, their study reported that quercetin treatment induced protein aggregation, mostly inside the nucleus [ 29 ]. Induction of autophagy by quercetin has been observed in several tissues and diseases, including diabetic nephropathy [ 30 ], oocytes from aged mice [ 31 ], intervertebral disc degeneration [ 32 ], myelodysplastic bone marrow [ 33 ], and human retinal pigment epithelial cells [ 34 ], while one study reported that quercetin attenuated autophagy in a rat model of traumatic brain injury [ 35 ]. Regardless of these previous studies, here we performed a comprehensive set of autophagy assays that unquestionably proved the effect of quercetin on autophagy for the first time [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of Janus Green B is an indirect method to assess mitochondrial dysfunction as the contents escape in the cytosol upon the rupture of the mitochondrial membrane, leading to colorant oxidation 10 . Briefly, the cells were stained with Janus Green B for 5 min, after which they were observed under an optical microscope (Axio Vert.A1, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Disease development and post treatment effects were confirmed by performing peripheral blood hemogram 36,39,46–48 . Total RBC and WBC counts were determined by standard laboratory protocol, using hemocytometer chamber (Rohem, India).…”
Section: Methodsmentioning
confidence: 99%